Innovative 21st-century teaching: effectiveness of pbl in enhancing 4c skills on genetic diversity - Indriyani, Dita; Siswati, Bea Hana; Savira, Nadyatul Ilma Indah (Biosfer: Jurnal Pendidikan Biologi, 2025)
Developing 4C skills (critical thinking, creativity, communication, and collaboration) is crucial for students' success, yet many Indonesian students still struggle to master these competencies. This study evaluates the impact of PBL on 10th-grade students' 4C skills in the genetic diversity topic at SMAN 3 Jember. Using a quasi-experimental design, 72 students were divided into control (36) and experimental (36) groups. Pre- and post-tests assessed critical and creative thinking, while communication and collaboration were observed directly. Data were analyzed with ANCOVA and Kruskal-Wallis tests in IBM SPSS Statistics 24.  The findings revealed significant improvement in the experimental group, moving from "poor" to "critical, creative, communicative, and collaborative," The control group showed only “modest” progress to "fair."  In conclusion, PBL is an effective approach to enhancing students' 4C skills, offering a valuable model for innovative teaching aligned with 21st-century education goals.